Active Vibration Control of a Flexible Spacecraft Structure - Agung, Rizqy; Kusni, Muhammad; Adhy Sasongko, Rianto; Eko Poetro, Ridanto; Gunawan, Leonardo; Akbar, Mahesa (FTMD Institut Teknologi Bandung, 2024)
In this paper, the spacecraft that evaluated has two motion mode, rigid body mode and flexible mode and it isoperated in low earth orbit. The rigid body mode is related to the attitude of spacecraft and flexible mode is relatedto vibration that occurs on the spacecraft structure. The vibration that occurs on the spacecraft structure may causeperformance degradation during operation. Hence, the active control vibration is applied to overcome the problemdue to the vibration phenomenon on spacecraft. The active control system was designed by using two methods,Pole-Placement Method and Linear Quadratic Regulator (LQR) Method, and those two methods are solved byusing numerical method. The result of Pole-Placement Method shows the vibration is reduce in less than 0.5 unitof time. Whereas, the most suitable control parameter input based on the LQR Method could reduce vibration inless than 8 unit of time. The LQR method provides more parameter variation; thus, the system could be controlledand adjusted due to its design requirement. Based on the LQR Method when the attenuation time is 8 unit of time,the energy required by the actuator is 84% less than that of the Pole-Placement Method.